2003
DOI: 10.1001/archneur.60.12.1760
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Clinical and Radiological Findings in Adults and Children With Japanese Encephalitis

Abstract: Children with JE are more likely to have dystonia and a poor outcome at 6 months compared with adults. The difference in clinical findings and outcome in children and adults with JE may be owing to immunological factors, maturation of the central nervous system, and neuronal plasticity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
2
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(84 citation statements)
references
References 12 publications
6
74
2
2
Order By: Relevance
“…10 Other imaging studies from India have not reported a high association of JE with NCC. 2,18 Our study found a significantly high prevalence of NCC in patients with JE (19.3%) in comparison with its prevalence in control subjects (1.04%). This high prevalence of NCC in JE is similar to the autopsy findings of some of the studies from India and China and is probably more than a chance coincidence.…”
Section: Discussionmentioning
confidence: 48%
“…10 Other imaging studies from India have not reported a high association of JE with NCC. 2,18 Our study found a significantly high prevalence of NCC in patients with JE (19.3%) in comparison with its prevalence in control subjects (1.04%). This high prevalence of NCC in JE is similar to the autopsy findings of some of the studies from India and China and is probably more than a chance coincidence.…”
Section: Discussionmentioning
confidence: 48%
“…47 A recently published study found that cranial CT was abnormal in around 38%, whereas MRI revealed pathological changes in 90.6 -95.5%. 48 Thalamic abnormalities on T2WI were found in 87.5% both in children and adults, in 40.6 -54.2% in the basal ganglia, in 28.1-45.8% in the midbrain and in 21.9 -25% in cortical areas.…”
Section: Viral Meningoencephalitismentioning
confidence: 98%
“…43,44 Other neurotropic flaviviruses cause St Louis encephalitis, West Nile virus, and Murray Valley encephalitis. As with other viruses in this family, many subclinical infections occur.…”
Section: Viruses: Encephalitis and Hemorrhagic Feversmentioning
confidence: 99%